Tumor microenvironment-activated theranostic nanoreactor for NIR-II photoacoustic imaging-guided tumor-specific photothermal therapy - Yang, Nan (2022)
Theranostic agents that can be sensitively and specifically activated by the tumor microenvironment (TME) have recently attracted considerable attention. In this study, TME-activatable 3,3′,5,5′-tetramethylbenzidine (TMB)-copper peroxide (CuO2)@poly(lactic-co-glycolic acid) (PLGA)@red blood cell membrane (RBCM) (TCPR) nanoparticles (NPs) for second near-infrared photoacoustic imaging-guided tumor-specific photothermal therapy were developed by co-loading CuO2 NPs and TMB into PLGA camouflaged by RBCMs. As an efficient H2O2 supplier, once exposed to a proton-rich TME, CuO2 NPs can generate H2O2 and Cu2+, which are further reduced to Cu+ by endogenous glutathione. Subsequently, the Cu+-mediated Fenton-like reaction produces cytotoxic ·OH to kill the cancer cells and induce TMB-mediated photoacoustic and photothermal effects. Combined with the RBCM modification-prolonged blood circulation, TCPR NPs display excellent specificity and efficiency in suppressing tumor growth, paving the way for more accurate, safe, and efficient cancer theranostics.